Synodality: Biblical Perspectives - Kakkanattu, Joy Philip; Mullooparambil, Sebastian (Asian Horizons, 2025)
This article discusses perspectives on Synodality in the Bible. It explores synodality traceable in the major sections of the Old Testament, with a focus on the creation of human beings, the covenant, and the prophetic literature. From the New Testament, passages and episodes are studied to understand synodality. From the Gospels, the communicative style of Jesus is explored. From the Acts, the election of Mathias, the appointment of the Seven Elders and the Jerusalem Council are analyzed. From the Pauline Corpus, the Case of the Incestuous Man (1 Cor 5:1–8, 13) and the Church as the body of Christ are discussed.